2004
DOI: 10.1016/j.atmosenv.2003.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Passive measurement of nitrogen oxides to assess traffic-related pollutant exposure for the East Bay Children's Respiratory Health Study

Abstract: The East Bay Children's Respiratory Health Study is examining associations between trafficrelated pollutant exposures and respiratory health among children who reside and attend schools at varied proximity to northern California freeways. Chronic exposures are being inferred from outdoor pollutant concentrations at neighborhood schools. This paper reports primarily weeklong integrated NO 2 and NO X concentrations measured with passive samplers placed outside at ten elementary schools during 14 weeks in spring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
36
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 17 publications
(20 reference statements)
3
36
0
Order By: Relevance
“…Indoor NO 2 concentrations reported for office [55] and resident [31] micro-environments were consistent with levels of theindoor NO 2 measure at Puta-Makhota toll plazas, while NO 2 concentrations at Sungai Besi and Kajang Toll plazas exceeded those reported in other studies by 3 to 4 times [20] [56]. The reason for such levels of pollution at toll plazas is possibly due to high levels of traffic density congestion which would rarely be found in residential areas.…”
Section: Comparison Of the Current Study With Other Studies And Worldsupporting
confidence: 48%
See 1 more Smart Citation
“…Indoor NO 2 concentrations reported for office [55] and resident [31] micro-environments were consistent with levels of theindoor NO 2 measure at Puta-Makhota toll plazas, while NO 2 concentrations at Sungai Besi and Kajang Toll plazas exceeded those reported in other studies by 3 to 4 times [20] [56]. The reason for such levels of pollution at toll plazas is possibly due to high levels of traffic density congestion which would rarely be found in residential areas.…”
Section: Comparison Of the Current Study With Other Studies And Worldsupporting
confidence: 48%
“…Meteorological factors such as wind, precipitation, humidity and temperature, influence the dispersion, deposition, transportation and transformation of nitrogen dioxide. Wind direction defines the direction of pollutant spatial distribution, while wind speed dictates the dispersion and deposition rate [19] [20]. High wind speed tends to reduce NO 2 concentration by aiding pollutant transportation and dispersion and vice versa in the direction of up-wind [21] [22].…”
Section: Factors That Influence No2 Concentrationmentioning
confidence: 99%
“…We found that the rank order (relative values) of the schools did not vary from week to week or season to season, supporting the validity of this approach. Additionally, the NO x and NO 2 concentrations at schools upwind or further from high traffic roads were similar to NO X and NO 2 concentrations measured at the closest fixed-site monitor (21). Although there may have been some changes in the absolute traffic volume on major roads in recent years, the principal traffic patterns in the area have not changed.…”
Section: Exposuresmentioning
confidence: 70%
“…The study average PM 2.5 (12 g/m 3 ) was similar to the annual average concentration of PM 2.5 at the central monitoring station, located approximately 15 km south of the study area. NO X and NO 2 measurements at the school sites away from traffic were similar to levels measured at the regional site (21). Table 3 summarizes the results of the two-stage hierarchical logistic regression models of the odds of asthma and bronchitis symptoms in the previous year in relationship to six different pollutants, each examined in separate regressions.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation